The Techniques and forms of the baroque imagination and the birth of modern science - Smart, Ángeles (2023)
The goal of this paper consists in connect the techniques and forms of the art´s symbolic production in the XVII´s century with some of the discourses and scientific progress of the same period. Following Severo Sarduy´s considerations and specially taking into account the case of Galileo, but also -although in a less way- that of Kepler and Descartes, I will follow the trail of the bonds between aesthetic attitude and scientific convictions in this thinkers in order to show the continuity of both dimensions in human existence. The presuppose is that the relation between though and expression is always dynamic and reciprocal: many ideas, theories and conceptual systems are innate with their related expressive shapes. At the same time in the variety of imaginative articulations we can find the presence and manifestation of different orders and meanings.